Altering Sterol Composition Implied That Cholesterol Is Not Physiologically Associated With Diosgenin Biosynthesis in Trigonella foenum-graecum - Cao, Liyang; Zhou, Zilin; Sun, Jia; Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2021)
Diosgenin serves as an important precursor of most steroidal drugs in market. Cholesterol was previously deemed as a sterol origin leading to diosgenin biosynthesis. This study reports that cholesterol is not in parallel with diosgenin biosynthesis in Trigonella foenum-graecum. We first perturbed its sterol composition using inhibitors specific for the upstream isoprenoid pathway enzymes, HMGR (3-hydroxy-3-methylgutaryl-CoA reductase) on the mevalonate (MVA) and DXR (1-deoxy-D-xylulose-5-phosphate reductoisoerase) on the 2-C-methyl-D-erythritol-4-phophate (MEP) pathways, and have revealed that diosgenin and cholesterol reversely or differently accumulated in either the MVA or the MEP pathway-suppressed plants, challenging the previously proposed role of cholesterol in diosgenin biosynthesis. To further investigate this, we altered the sterol composition by suppressing and overexpressing the 24-sterol methyltransferase type 1 (SMT1) gene in T. foenum-graecum, as SMT1 acts in the first committed step of diverting the carbon flux of cholesterol toward biosynthesis of 24-alkyl sterols. Knock down of TfSMT1 expression led to increased cholesterol level but caused a large reduction of diosgenin. Diosgenin was increased upon the TfSMT1-overexpressing, which, however, did not significantly affect cholesterol biosynthesis. These data consistently supported that diosgenin biosynthesis in T. foenum-graecum is not associated with cholesterol. Rather, campesterol, a 24-alkyl sterol, was indicative of being correlative to diosgenin biosynthesis in T. foenum-graecum.